Communication, consumption and sustainability: An analysis from the environmental perspective (Research, Society and Development, 2021)
Consumption and sustainability are a current theme in our society that sparks a latent problem in our society today, and that has brought up a discussion about the importance of raising awareness of sustainable consumption. We are all part of an ecosystem that every day generates an often involuntary departure from our green. Without realizing it, the communication of companies focused on the search for better results, encourages accelerated consumption as a way to generate greater profits and “heating up” the sales of their products and services, always at a pace of continuous growth. The search for ever-greater profits ignores the basic fact that to meet this demand, companies have been ignoring the preservation of the planet, which cannot regenerate at the same speed as it supplies the raw material needed to meet the production of these products. As an ally of companies in this process of encouraging consumption, strategic communication is more efficient and increasingly provided with specific channels of common interests, reaching its target audience more assertively, thus encouraging even greater consumption by these groups. In this way, the need to have an equation between consumption and environmental preservation, is present so that there is a balance as a determining factor in the awareness of consumers to maintain, in a sustainable way, the resources necessary for the survival of humanity. The need to use communication as a preponderant factor with the important function of generating people's awareness, and consequently, educating the population about the urgent need for new consumption habits is essential to regenerate the damage caused to the planet over time.